Surface modification of ultrafine‐grained titanium: Influence on mechanical properties, cytocompatibility, and osseointegration potential. Issue 1 (4th January 2019) - Pippenger, Benjamin E.; Rottmar, Markus; Kopf, Brigitte S.; Stübinger, Stefan; Dalla Torre, Florian H.; Berner, Simon; Maniura‐Weber, Katharina
Abstract: Objective: The main objective of this study was to demonstrate that dental implants made from ultrafine‐grain titanium (UFG‐Ti) can be created that replicate state of the art surfaces of standard coarse‐grain titanium (Ti), showing excellent cytocompatibility and osseointegration potential while also providing improved mechanical properties. Material and methods: UFG‐Ti was prepared by continuous equal channel angular processing (ECAP), and surfaces were treated by sandblasting and acid etching. Mechanical properties (tensile and fatigue strength), wettability, and roughness parameters were evaluated. Human trabecular bone‐derived osteoblast precursor cells (HBCs) were cultured on all samples to examine cytocompatibility and mineralization after 4 and 28 days, respectively. Biomechanical pull‐out measurements were performed in a rabbit in vivo model 4 weeks after implantation. Results: Both yield and tensile strength as well as fatigue endurance were higher for UFG‐Ti compared to Ti by 40%, 45%, and 34%, respectively. Fatigue endurance was slightly reduced following surface treatment. Existing surface treatment protocols could be applied to UFG‐Ti and resulted in similar roughness and wettability as for standard Ti. Cell attachment and spreading were comparable on all samples, but mineralization was higher for the surfaces with hydrophilic treatment with no significant difference between UFG‐Ti and Ti. Pull‐out tests revealed that osseointegration of surface‐treated UFG‐Ti was found to be similar to that of surface‐treated Ti. Conclusion: It could be demonstrated that existing surface treatments for Ti can be translated to UFG‐Ti and, furthermore, that dental implants made from surface‐treated UFG‐Ti exhibit superior mechanical properties while maintaining cytocompatibility and osseointegration potential.